Philip P. Betancourt (ed.). Temple University Aegean Symposium: a compendium - Dickinson, Oliver (Journal of Greek Archaeology, 2016)
This work forms a compilation of the typewritten texts prepared by the speakers and copied, to be bound into volumes for distribution to attendees at the Aegean Symposium held annually at Temple University, Philadelphia, from 1976 to 1985. Thus they vary somewhat in font and spacing on the page, and since the texts could not be edited minor errors like typos are noticeable, but they are not common. Some are the equivalent of articles, but others are so short that one imagines they can only have been intended as guides to what the speaker was going to say. Usually there are bibliographies, and often footnotes, and some are illustrated with line drawings, which may be reproductions of previously published illustrations and plans, or prepared for the seminar paper.